Beyond the baby schema: Objects being touched are perceived to be cute - Akane Ohashi; Hiroshi Nittono (PLoS ONE, 2026)
Research on cuteness has traditionally focused on the baby schema, which is used to describe the physical characteristics of an individual. Recent research, however, has shown that the characteristics of interactions between individuals, such as physical contact and social relationships, can also be perceived as cute (or kawaii in Japanese) and evoke a special feeling associated with its perception. In this study, we aimed to examine the influence of seeing an object being touched by another person on impressions of cuteness or kawaii by manipulating the level of the baby schema features. Online surveys were conducted in Japan ( n = 198) and the United States ( n = 199). Participants were presented with four photographs depicting a person holding or not holding an object with high or low baby schema features and were asked to rate their feelings of cuteness or kawaii toward the object. In addition, following the procedures of previous research, they were asked to report their impression of the person in the photograph and their guess about how the person felt about the object. The results showed that the objects with higher baby schema features and the objects being touched were rated as cuter or more kawaii. These effects did not interact. Similar effects were observed for the cuteness ratings of the person and guesses about the person’s feelings. The present study suggests that the perceived cuteness of an object is influenced not only by its baby schema characteristics but also by factors such as physical contact or the relationship between the entities.